Gestión de ventas y la rentabilidad en la empresa Icoplast periodo 2022-2023 - Ramirez Carrasco, Nayeli Germania (2024)
ABSTRACT: The research SALES MANAGEMENT AND PROFITABILITY IN ICOPLAST COMPANY DURING THE PERIOD 2022-2023 is a study that aims to evaluate the company's sales management and its impact on profitability for the specified period. This research seeks to propose strategies that enable optimization of both aspects. The research methodology includes a quantitative analysis, followed by a survey instrument and financial indicators to collect data. The collected data were tabulated and presented in tables and statistical graphs, allowing for the analysis and interpretation of results extracted from the primary source. Also, the hypothetical-deductive method was essential to test the alternative hypothesis using the SPSS system to optimize processes and increase profitability. Sales management plays a crucial role in organizing and supervising the sales process, improving operational efficiency, and establishing reliable relationships with customers, which are vital for the overall success of a company. On the other hand, a company's profitability refers to its ability to generate earnings compared to the resources invested, which is essential for its long-term growth and sustainability. The research work also addresses related concepts such as cash surpluses, temporary and permanent investments, pre-sale and post-sale stages, inventory management, sales team, profitability and its characteristics, ratios, advantages and disadvantages, market share, competitors, technology and machinery, billing, strategic alliances, human capital, pricing strategy, resources, and innovation.